Eating culture among ASEAN countries and its implication towards development of regional Halal industries - Ab. Rahman, Suhaimi; Abdul Rahman, Russly; Ab. Majid, Mahmood Zuhdi; Deuraseh, Nurdeng; Ramli, Mohd Anuar; Jamaludin, Mohammad Aizat (2014)
Halal industries play important roles in developing Malaysian economy with its halal product export reached RM7768.4 million from January to March this year alone. The main halal exports are food ingredients which valued for RM2521.9 million, followed by food and beverages which valued for RM3140.8 million and fats and oil derivatives account for RM1449.2 million. Malaysia is now leading in development and establishment of halal certification and became center of references for other country’s certification bodies. With broad export market and variety of resources it creates a brighter sight for Malaysia to be one of the biggest halal exporters in ASEAN. Despite the opportunity and the strength that Malaysia has in halal market, several loopholes which badly affect the halal product export need to be addressed. These include the inadequate information on legislation, social and culture of the importing countries that contribute to fewer acceptances of the exported products. Malaysian industries tend produce food products without proper knowledge of consumer acceptance in their respective importing countries. This paper is an attempt to explore the eating cultures among selected ASEAN countries and its implication on the development of the regional halal industries. Several ASEAN countries which include Malaysia, Indonesia and Thailand have been targeted as the respondents for this study. Data was collected from both documents and an in-depth interview with experts from respective countries. Findings show that local preferences on food products is related to several factors which include socio-economics, religion, age, education, social class and the place of culture itself. Different culture in different countries creates a different preference in food consumption. The paper concludes that in order to penetrate the halal products into different ASEAN countries both the producers and the exporters need to understand the local preferences and cultures on food products before embarking into the business.